(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, whose grace has no limit, and there is no limit to his generosity, and prayers and peace be upon the Seal of His Prophets and Messengers, and upon his family and companions, and after:Since the Book of God Almighty is miraculous in its letters, words, and verses, we wanted to stop at two terms that were repeated in many places in it, and they are (haste and haste). In this research, therefore, our research came divided into two sections, the first of which is: dealing with haste in language and terminology, and what is indicated by the derivatives of this term in the contexts in which it was mentioned in the Quranic verses.